How to manage processing in archives and special collections - Hackbart-Dean, Pam; Slomba, Elizabeth; Society of American Archivists (Chicago, IL Society of American Archivists, 2012)
Primarily directed at beginning archivists, and those working at colleges with limited professional staff or even a sole employee, this book includes material useful in a variety of settings. It has a strong management focus, but also gives space to adapting to standards and relatively new innovations such as Web 2.0. But the overall goal of any special collection is to provide useful material to patrons as quickly as feasible, while having in place solid protective measures--and this work never loses that focus. Written by Hackbart-Dean (Special Collections Research Center, Southern Illinois U.) and Slomba (archivist, U. of New Hampshire), it closes with a bibliographic essay on subjects like book processing costs and backlog management. An appendix providing sample forms for preparing one's own processing work plan is also included. Annotation ©2012 Book News, Inc., Portland, OR (booknews.com)
Includes bibliographical references and index
Keywords: Archives -- Processing; Archives -- Administration